Medical Geochemistry Geological Materials and Health - Censi, Paolo.; Censi, Paolo.; Darrah, Thomas.; Darrah, Thomas.; Erel, Yigal.; Erel, Yigal. (Springer Netherlands : Imprint: Springer, 2013)
This book includes a collection of chapters illustrating the application of geochemical methods to investigate the interactions between geological materials and fluids with humans. Examples include the incorporation and human health effects of inhaling lithogenic materials, the reactivity of biological fluids with geological materials, and the impact on nascent biomineral formation. Biomineralization is investigated in terms of mineralogy, morphology, bone chemistry, and pathological significance with a focus on the health impacts of "foreign" geological/environmental trace element incorporation. One of the contribution is devoted to particulate matter, the presence of metals and metalloids in the environment, and the possibility of using human hair as a biomarker between environmental/geological exposure and human bioincorporation. Other chapters focus on the last advances on the analytical methods and instrumentational approaches to investigating the chemistry of biological fluids and tissues.